PAIRWORK IS A SUCCESSFUL TEACHING STRATEGY IN LANGUAGE CLASSES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
It is noteworthy to note that students get a lot of knowledge when they work in groups since they have more opportunities to connect. The best technique to gauge students' learning progress is through pair work. The teacher can accomplish this without the kids being aware that they are being watched and tested. Working in pairs increases the learners' linguistic productivity since it deepens and fosters a meaningful connection between them. The teacher cannot listen to all couples at once in the interim, but that does not mean that nothing can be done about it.